The Effect of Earning Per Share (EPS), Price Earning Ratio (PER), and Price To Book Value (PBV) on Stock Returns in Automotive Sub-Sector Companies - Mutiara Gita Dwinanda; Rina Maria Hendriyani (Fakultas Bisnis, 2022)
This study aims to examine and analyze the Effect of Earning Per Share (EPS), Price Earning Ratio (PER), And Price To Book Value (PBV) Against Stock Returns in Automotive Sub-Sector Companies listed on the Indonesia Stock Exchange in 2017-2021.This research was conducted using quantitative methods with a descriptive, verification approach. The sample of this research is 5 companies from 13 companies, with a total of 25 samples obtained by purpose sampling technique. The information examination method utilized in this study is various straight relapse investigation with PC program devices utilizing Microsoft Succeed 2010 and the IBM SPSS Measurements form 25 application.The consequences of this concentrate to some degree show that the EPS variable makes a positive difference, while the PER and PBV factors meaningfully affect Stock Return . At the same time, EPS, PER, and PBV have a beneficial outcome of 62.3% on Stock Return while the leftover 37.7% is impacted by factors not inspected.